2020
DOI: 10.21203/rs.3.rs-21459/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical significance of peripheral blood-derived inflammation markers in advanced gastric cancer after radical resection

Abstract: Background and objective: The prognostic significance of peripheral blood-derived inflammation markers in patients with gastric cancer (GC) has not been elucidated. This study aimed to investigate the relationship between systemic inflammatory markers and GC prognosis. Methods:A prospective observational cohort study involving 598 patients was conducted to analyze the prognosis of GC based on systemic inflammatory markers. The following peripheral blood-derived inflammation markers were evaluated: the neutroph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…SII is an integrated indicator based on peripheral lymphocyte, neutrophil, and platelet counts, and may better reflect the balance of host inflammatory and immune status. Shi et al reported that compared with other systemic inflammatory indices, SII was a reliable index for predicting postoperative survival of GC (33), while Gu et al reported a higher PLR (34), and Zhang et al reported an elevated NLR and PLR were also reliable (35). Wu et al found GC patients with high fibrinogen and low albumin had a poor prognosis, and that FAR was an independent prognostic factor for recurrence after radical resection in GC patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…SII is an integrated indicator based on peripheral lymphocyte, neutrophil, and platelet counts, and may better reflect the balance of host inflammatory and immune status. Shi et al reported that compared with other systemic inflammatory indices, SII was a reliable index for predicting postoperative survival of GC (33), while Gu et al reported a higher PLR (34), and Zhang et al reported an elevated NLR and PLR were also reliable (35). Wu et al found GC patients with high fibrinogen and low albumin had a poor prognosis, and that FAR was an independent prognostic factor for recurrence after radical resection in GC patients (36).…”
Section: Discussionmentioning
confidence: 99%